Distribution and abundance of the South American sea lion Otaria flavescens (Carnivora: Otariidae) along the central coast off Chile Distribución y abundancia del lobo marino común Otaria flavescens (Carnivora: Otariidae) en la costa de Chile central - MARITZA SEPÚLVEDA (Revista Chilena de Historia Natural, 2011)
The onshore distribution and abundance of the South American sea lion Otaria flavescens along the central Chilean coast was estimated during the period January-February 2007. Additionally, changes in population abundance during the period 1970-2007 were examined. Population surveys were based on photographs taken from boats or aircraft. A total of 16301 sea lions (CI = 16209-16375) were counted in 33 colonies (6 breeding and 27 non-breeding sites). After correction to account for the proportion of individuals at sea and for pups not seen at the time of the survey, the mean estimated abundance was 18179 (95 % CI = 17777-18851) sea lions. Population trend analysis showed that from 1970 to 1985, South American sea lions showed a positive increase of approximately 2.1 % yr-1. Nevertheless, between 1985 and 1997 and between 1997 and 2007, the estimated number of sea lions showed a stable or slightly negative trend of 0.4 ± 0.1 % yr-1and 0.5 ± 0.1 % yr-1, respectively. We suggest that the overexploitation and decline of the principal fisheries in Central Chile could adversely impact the abundance and distribution of the South American sea lion in the study area. Se estimó la distribución y la abundancia poblacional del lobo marino común Otaria flavescens en la costa de Chile central durante los meses de enero y febrero de 2007. Adicionalmente, se analizaron los cambios en la abundancia de esta especie durante el período 1970-2007. Los censos poblacionales se basaron en fotografías tomadas desde embarcaciones menores o desde avionetas. Se contabilizaron un total de 16301 lobos marinos (IC = 16209-16375) en 33 colonias (6 reproductivas y 27 no reproductivas). Después de corregir por la proporción de animales en el agua y por crías no registradas al momento del censo, se estimó una abundancia promedio de 18179 (95 % CI = 17777-18851) lobos marinos en el área de estudio. El análisis de tendencia poblacional presentó que desde 1970 a 1985 la abundancia-lobo marino com-mostró una tendencia positiva de aproximadamente 2.1 % año-1. Sin embargo, entre 1985 a 1997, y entre 1997 a 2007, el número de lobos marinos muestra una tendencia estable o ligeramente negativa de 0.4 ± 0.1 % año-1 y 0.5 ± 0.1 % año-1, respectivamente. Se sugiere que la sobreexplotación y la declinación de las principales pesquerías en la zona central de Chife podría haber impactado negativamente la distribución y abundancia del lobo marino común en el área de estudio.